The impact of cognitive incompatibility schemes on the development of creative thinking skills in history subjects among first grade students (Journal of the College of Education for Women, 2019)
The aim of this research is to find out the impact of cognitive incompatibility schemes on the development of creative thinking skills among first grade students.To prove the objective of the research, the researcher put the following hypothesis:There is no statistically significant difference at the level of (0.05) between the average score of the experimental group who study the history of ancient civilizations according to the patterns of cognitive conflict and the average grades of the control group students who study the same subject in the usual way in the test of post-creative thinking skill